2014
DOI: 10.1007/s00240-014-0730-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative infectious complications following percutaneous nephrolithotomy: a prospective clinical study

Abstract: The aim of the study was to assess the preoperative and intraoperative potential risk factors for infectious complications after percutaneous nephrolithotomy (PCNL). A total of 303 patients who underwent PCNL for renal stones were included in the recent study. A detailed history including past renal surgery, nephrostomy insertion and recurrent urinary infection were obtained from all patients. Preoperative urine culture, renal pelvic urine culture and stone culture were obtained from all patients. The intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 22 publications
11
75
4
2
Order By: Relevance
“…Several recent studies of PCNL that have been undertaken worldwide have reported major complication rates as follows: systemic inflammatory response syndrome in 27.4%, sepsis in 7.6%, severe bleeding in 7.8%, blood transfusions in 5.7%, renal pelvis perforations in 3.4%, severe hemorrhages requiring hemostasis procedures in 2.3%, and hydrothorax in 1.8% of cases, respectively. [26][27][28] Complications were observed at rather lower rates in our study compared with these reports, which may be associated with the safety of the ECIRS procedure itself when it is undertaken in the modified Valdivia position. Another reason underlying the lower complication rates in the present study relates to the operation plans often changing from single sessions to staged ECIRS in complicated situations, including those in which the field of view could not be secured as a consequence of severe bleeding.…”
Section: Commentcontrasting
confidence: 75%
“…Several recent studies of PCNL that have been undertaken worldwide have reported major complication rates as follows: systemic inflammatory response syndrome in 27.4%, sepsis in 7.6%, severe bleeding in 7.8%, blood transfusions in 5.7%, renal pelvis perforations in 3.4%, severe hemorrhages requiring hemostasis procedures in 2.3%, and hydrothorax in 1.8% of cases, respectively. [26][27][28] Complications were observed at rather lower rates in our study compared with these reports, which may be associated with the safety of the ECIRS procedure itself when it is undertaken in the modified Valdivia position. Another reason underlying the lower complication rates in the present study relates to the operation plans often changing from single sessions to staged ECIRS in complicated situations, including those in which the field of view could not be secured as a consequence of severe bleeding.…”
Section: Commentcontrasting
confidence: 75%
“…2,6,9,15 Several publications have also attempted to evaluate prognostic factors for complications after percutaneous nephrolithotomy. 3,4,6,7,15,16,18,19,24 A failure to use a standardized reporting classification system has made interpretation and comparison of results difficult. To address this issue the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT modified Clavien scoring system has been assessed and is now recommended for use when reporting endourological surgery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various publications have assessed several clinical, radiological and perioperative variables for their potential influence on postoperative complications. [2][3][4][5][6] Unfortunately, only a few published reports used a specific complication score for urological surgery. 7,8,9 Moreover, until recently, there was a lack of standardization of PCNL reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, we consider that the microbiological investigation of the calculi may be an important investigation, as the bacteria that colonize the calculi can induce bacteriuria/UTI, or even inflammatory response syndrome and sepsis when certain conditions are met (15). The presence of this association, left without an adequate treatment (such as the calculi-free status and proper antibiotherapy) can lead patients to develop recurrence of urolithiasis or even struvite urolithiasis, with wellknown consequences for the urinary system and for the entire human body.…”
Section: Discussionmentioning
confidence: 99%